Strategies for Improving the English Competence of Vocational High School Students at SMK Sritanjung Banyuwangi - Doni Hadi Irawan; Muhamad Alfi Khoiruman (Institut Teknologi Pendidikan Indonesia, 2026)
English competence is increasingly important for vocational high school students because it supports academic development, workplace communication, and readiness to compete in national and international labor markets. However, many vocational students face difficulties in developing their English competence due to limited vocabulary, insufficient exposure to English, low confidence, limited opportunities for meaningful interaction, and teaching practices that emphasize memorization and theoretical knowledge. Similar challenges have been identified at SMK Sritanjung Banyuwangi, where students often remain passive and hesitant to use English actively in classroom activities. Therefore, this study aims to explore and analyze strategies for improving the English competence of vocational high school students at SMK Sritanjung Banyuwangi. The study focuses on context-based strategies, including English for Specific Purposes (ESP), communicative language teaching, interactive activities, role play, project-based learning, authentic vocational materials, technology integration, and competency-based assessment. These strategies are expected to connect English learning with students’ vocational needs and future professional contexts while enhancing motivation, confidence, vocabulary knowledge, and practical communication skills. The findings are expected to contribute to more effective English teaching strategies in vocational education and prepare students for future academic, professional, and global communication challenges.